Fenologia da floração e biologia da polinização de herbáceas e arbusto em área de restauração ambiental no semiárido - Rodrigues, Rafael Maia (2019)
Pollination is one of the most important processes for ecosystems, for example, it is an essential right for the survival of living beings. Your decline should take a reduction of the food of the animals and, consequently, one effect in cascade, influencing dynamically the distant and containingting the las pretty. Information about the availability of flowers and the action of pollinators can provide important subsidies to environmental recovery programs. The objective of this study was to investigate which species are most attractive to floral visitors in an urban area at an early stage of recovery in the municipality of Mossoró - RN, Northeast Brazil. The study was carried out at the Federal Rural University of the Semi-Arid (UFERSA) Campus, located at Av. Francisco Mota, 572 - Bairro Costa e Silva - Mossoró - RN. Flowering observations were carried out in an area of approximately 0.5 ha on the west campus of UFERSA, with predominant herbaceous vegetation. We randomly selected 10 individuals from each species that occurred naturally within or around 10 plots of 1m2. The monitoring of the species occurred biweekly, in the period between March 2017 and February 2018, for floral phenology. It was determined the period of occurrence and intensity of flowering of the species and the thermal window for each plant species, which determined the temperature range that each plant species received floral visitors. 11 plant species were observed, being 10 herbaceous and one shrub, distributed in five families and in nine different genera. All species showed seasonal flowering with all individuals presenting flowers and floral buds at one time of the year. Flowering of the species occurred between the months of in all months of the study. The flowering was correlated mainly with the precipitations of the current month and with precipitation of the previous month. The five plant species that received the most visits (Passiflora foetida L., Boerhavia diffusa L., Merremia aegyptia (L.) Urb., Neptunia plena (L.) Benth. And Turnera subulata Sm.) Accounted for more than 92% of total number of visits observed in the study. These visits occurred in a range of 21 ° C to 33 ° C among all species with peak visits between 23.5 ° C and 27.7 ° C with small variations between species. Nine species of floral visitors were found distributed in three different orders: Himenóptera, Lepidóptera and Díptera, with main group of floral visitors, in number of species and number of visits was the bees. These visits were correlated with the maximum and average temperatures, the relative humidity of the maximum and average air, with the richness of visitors, riches of plants and with the precipitations of the current month and the previous month. For temperatures, Spearman's Correlation Coefficient was negative for the maximum temperature in relation to the number of flowers